THE IMAGE OF “AN ORDINARY AMERICAN” IN J. UPDIKE’S SHORT STORIES - Olena Bezhan (Scientific Journal of Polonia University, 2023)
The article is devoted to the study of the short story genre in the context of the second half of the twentieth century American literature, an attempt is made to show the way of the genre from the form of standard story to so called “psychological sketch”. The short story manifested the national originality of American prose, the peculiarities of the national character and local color earlier and more fully than other forms. It developed the traditions of folk stories, folk humor, and satire. The object of analysis is J. Updike’s short story "Pigeon Feathers", that is concentrated on the middle class problems of American society and the “ordinary Americans”. Updike became an innovator in the short story genre, embodying the best ideas of his predecessors and developing his own ideas of genre diversity. According to both national and American critics, the main stylistic feature of Updike's short story collections is the close connection between them, most of them continuing each other, leaving behind a through plot and a single emotional experience.